Implementing the National Heart, Lung, and Blood Institute's Strategic Vision in the Division of Cardiovascular Sciences—2022 Update. Issue 8 (30th September 2022) - Grant, Meagan G.; Pratt, Charlotte; Wong, Renee P.; Addou, Ebyan; Desvigne-Nickens, Patrice; Campo, Rebecca A.; Donze, Laurie Friedman; Barnes, Vanessa I.; Schopfer, David W.; Jaquish, Cashell E.; Fleg, Jerome; Galis, Zorina S.; et al.
Abstract : Spurred by the 2016 release of the National Heart, Lung, and Blood Institute's Strategic Vision, the Division of Cardiovascular Sciences developed its Strategic Vision Implementation Plan—a blueprint for reigniting the decline in cardiovascular disease (CVD) mortality rates, improving health equity, and accelerating translation of scientific discoveries into better cardiovascular health (CVH). The 6 scientific focus areas of the Strategic Vision Implementation Plan reflect the multifactorial nature of CVD and include (1) addressing social determinants of CVH and health inequities, (2) enhancing resilience, (3) promoting CVH and preventing CVD across the lifespan, (4) eliminating hypertension-related CVD, (5) reducing the burden of heart failure, and (6) preventing vascular dementia. This article presents an update of strategic vision implementation activities within Division of Cardiovascular Sciences. Overarching and cross-cutting themes include training the scientific workforce and engaging the extramural scientific community to stimulate transformative research in cardiovascular sciences. In partnership with other NIH Institutes, Federal agencies, industry, and the extramural research community, Division of Cardiovascular Sciences strategic vision implementation has stimulated development of numerous workshops and research funding opportunities. Strategic Vision Implementation Plan activities highlight innovative intervention modalities, interdisciplinary systems approaches to CVD reduction, a life course framework for CVH promotion and CVD prevention, and multi-pronged research strategies for combatting COVID-19. As new knowledge, technologies, and areas of scientific research emerge, Division of Cardiovascular Sciences will continue its thoughtful approach to strategic vision implementation, remaining poised to seize emerging opportunities and catalyze breakthroughs in cardiovascular sciences.